China's route heritage : mobility narratives, modernity and the Ancient Tea Horse Road - Sigley, Gary (Abingdon, Oxon ; New York : Routledge, 2021)
"China's Route Heritage examines the creation, development and proliferation of the route heritage discourse of chama gudao, The Ancient Tea Horse Road (ATHR), in the People's Republic of China. Examining the formation of the tea road as a concept, its development as a platform for cultural branding, and its most recent interactions with the policy of the Belt and Road Initiative (BRI) and the revival of the discourse on the Silk Roads, the book demonstrates that the ATHR is an important part of the discourse on Chinese modernity. Describing the route heritage of the ATHR as a 'mobility narrative', whereby an ancient route is used to form a narrative of ethnic unity and cooperation, the book demonstrates that the study of such heritage offers unique insights into issues that are of concern to the wider field of critical heritage studies. Sigley also shows how the study of alternative route heritage enables us to gain a broader sense of route heritage discourse and its implications for the discussion of historical, present and future forms of mobility and connectivity within China and beyond its borders. China's Route Heritage should be of interest to researchers and postgraduate students who are engaged in the study of heritage, China, the Silk Roads and the BRI, politics, international relations and tourism"--
Chinese Culture and the 'Great Revival of the Chinese Nation': From Silk Road to Belt and Road -- The Physical and Cultural Geography of Southwest China's Ancient Tea Horse Road: Muleteers, Mountains and Mobility -- Modernity, Territoriality and the Terraformation of Yunnan: From Tianxia to Nation-State -- The Creation and Proliferation of a Route Heritage Mobility Narrative of Southwest China: The 'Old Ancient Tea Horse Road' -- Touristic Modernity and the Simulacrum: The Invention of the 'New Ancient Tea Horse Road' -- Tea-Horse Road Tourism, Theme Parks and Themed Residential and Commercial Spaces: The 'New Ancient Tea Horse Road' and Global Modernity -- Epilogue: Mobility and the 'Modern World': Revisiting the Dulong Road.
OCLC-licensed vendor bibliographic record.
Keywords: Trade routes -- China, Southwest -- History; Heritage tourism -- China -- Yunnan Sheng; Ancient Tea Horse Road -- History; Yunnan Sheng (China); HISTORY / Asia / China; HISTORY / Asia / General